An ALMA survey of submillimetre galaxies in the COSMOS field: Physical properties derived from energy balance spectral energy distribution modelling - Miettinen, O.; Delvecchio, I.; Smolcic, V.; Aravena, M.; Brisbin, D.; Karim, A.; Magnelli, B.; Novak, M.; Schinnerer, E.; Albrecht, M.; Aussel, H.; Bertoldi, F.; et al. (EDP Sciences, 2017)
Context. Submillimetre galaxies (SMGs) represent an important source population in the origin and cosmic evolution of the most massive galaxies. Hence, it is imperative to place firm constraints on the fundamental physical properties of large samples of SMGs.